Activity of GS-linked chimeric endolysin CHAPk-SH3bk against methicillin-resistant Staphylococcus aureus biofilms: an in-vitro, ex-vivo and in-vivo study - Manisha Behera; Priyanka Singh; Anita Kamra Verma; Sachinandan De; Soma M. Ghorai (npj Biofilms and Microbiomes)
Abstract The evolution of antibiotic resistance and the propensity of methicillin-resistant Staphylococcus aureus to form biofilms impedes antibiotic therapy, which enkindles the rummage for novel therapeutic agents like bacteriophage endolysins. This study investigates the biofilm degradation activity of novel chimeric endolysin CHAPk-SH3bk compared to single domain construct CHAPk. The in-vitro biofilm degradation assay displayed higher antibiofilm activity of CHAPk-SH3bk compared to CHAPk on glass and steel surfaces. Treatment of CHAPk-SH3bk effectively inhibited biofilm formation of hospital-associated and bovine-origin MRSA. The in-vivo results displayed a higher reduction of 24 h MRSA-biofilm using CHAPk-SH3bk compared to CHAPk in mice skin infection model. Further, confocal laser scanning microscopy, scanning electron microscopy, and immunohistochemistry confirmed the in-vivo results. The study indicated that attachment of SH3b using glycine-serine linker to CHAPk increased the catalytic domains biofilm reduction ability. The study demonstrates that construction of novel chimeric endolysins by shuffling parental endolysin domains may increase their antibiofilm activity.